Novel KIAA0753 mutations extend the phenotype of skeletal ciliopathies. Issue 1 (December 2017) - Hammarsjö, A.; Wang, Z.; Vaz, R.; Taylan, F.; Sedghi, M.; Girisha, K.; Chitayat, D.; Neethukrishna, K.; Shannon, P.; Godoy, R.; Gowrishankar, K.; Lindstrand, A.; et al.
Abstract The skeletal ciliopathies are a heterogeneous group of disorders with a significant clinical and genetic variability and the main clinical features are thoracic hypoplasia and short tubular bones. To date, 25 genes have been identified in association with skeletal ciliopathies. Mutations in theKIAA0753 gene have recently been associated with Joubert syndrome (JBTS) and orofaciodigital (OFD) syndrome. We report biallelic pathogenic variants inKIAA0753 in four patients with short-rib type skeletal dysplasia. The manifestations in our patients are variable and ranging from fetal lethal to viable and moderate skeletal dysplasia with narrow thorax and abnormal metaphyses. We demonstrate that KIAA0753 is expressed in normal fetal human growth plate and show that the affected fetus, with a compound heterozygous frameshift and a nonsense mutation inKIAA0753, has an abnormal proliferative zone and a broad hypertrophic zone. The importance ofKIAA0753 for normal skeletal development is further confirmed by our findings that zebrafish embryos homozygous for a nonsense mutation inkiaa0753 display altered cartilage patterning.